If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x(2x + 3) = 2x(-4 + 3) Reorder the terms: -1x(3 + 2x) = 2x(-4 + 3) (3 * -1x + 2x * -1x) = 2x(-4 + 3) (-3x + -2x2) = 2x(-4 + 3) Combine like terms: -4 + 3 = -1 -3x + -2x2 = 2x(-1) Reorder the terms for easier multiplication: -3x + -2x2 = 2 * -1x Multiply 2 * -1 -3x + -2x2 = -2x Solving -3x + -2x2 = -2x Solving for variable 'x'. Reorder the terms: -3x + 2x + -2x2 = -2x + 2x Combine like terms: -3x + 2x = -1x -1x + -2x2 = -2x + 2x Combine like terms: -2x + 2x = 0 -1x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '-1x'. -1x(1 + 2x) = 0 Ignore the factor -1.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {0, -0.5}
| 6x+28=21x+18 | | 18(x+2)=3(6x+5)+21 | | 3c+4=9+c | | sin(x+45)=2sinx | | 9(x+5)+6=-21 | | 13=x^3-14 | | lx-2l=5x+14 | | a+17+4a-8= | | 4h+12=8k | | 3x+29x-1=4x+4 | | 4x-8-3x-2=3x-2x-13 | | 3(23-24)=(24-6) | | 9+X-4X=24 | | -256/16= | | 2.5(2z+2.5)=5(z+2.5) | | 5x=2x+72 | | f(13)=x^3-14 | | 36-18n+9n=18 | | 1000000=x(12-.025x) | | [(4x^2)-6]+[(-2x^2)+19x]=180 | | X(4.8)=6(5)-6x | | 23+9=4b+66 | | 2m^7-7m+6=0 | | 2x-7=1x-2 | | 0.5x+11-x=0.6x+0.3 | | 6+6r=66 | | 15=0.6f | | 2w+6=10 | | 5(m-3)-4(m+2)=-23 | | 4+105x+5=-0.08571428571 | | (2x^2)+13x=180 | | 5x-(x+4)=8 |